CLINICAL AND SOCIO-DEMOGRAPHIC PROFILE OF EXTRAPULMONARY TUBERCULOSIS AT TERTIARY CARE CENTRE. - Dr. Pala Anil Kumar Reddy; Dr. Neelima S. Deshpande; Dr. Abhijeet M. Yadav; Dr. Gajanan V. Halkanche; Dr. Uday S. Mohite (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Tuberculosis remains a major global health problem with 1/3 of world’s population being infected with tuberculosis. Along with HIV, Diabetes mellitus and recently evolved drug resistant tuberculosis, it is a big threat for mankind. TB can involve any organ system in the body. While Pulmonary TB is the most common presentation, Extra pulmonary TB is also an important clinical problem. Material and methods: A cross sectional study were conducted in General Medicine department of a tertiary care hospital after ethics committee permission.  100 Extra pulmonary TB patients who came to our general medicine OPD and Inpatient admissions, who fulfilled the inclusion criteria were considered for the study over a period of 18 months. Result: Out of 100 Extra pulmonary TB cases, 56 were males (56%) and 44 were females (44%). Pleura TB (32%) and lymph node TB (29%) were the most common Extra pulmonary TB diagnosis followed by abdominal TB (18%), Pott’s spine (11%), Genital TB (5%), TB meningitis (4%), Peritoneal TB (1%). 78 cases recovered, 12 cases were lost to follow up, 10 cases died during the study. Mortality was high in Abdominal TB (27.8%) followed in frequency by Potts’s spine (27.3%) and TB meningitis (25%). HIV positive status increased the mortality rateConclusion: Extra pulmonary tuberculosis remains a significant health issue in developing Countries. Extra pulmonary TB contributes a significant share for TB burden, however unnoticed. Our study enhances the knowledge regarding the epidemiology of Extra pulmonary TB and expands understanding of the relative contribution of host related factors to its pathogenesis. The frequency of Extra pulmonary TB in this study was higher with the highest proportion contributed by both pleural TB and lymph node TB. Moreover, being male patient was at higher rate of positivity for Extra pulmonary TB than female. Age group 20-50 years, associated diabetes mellitus, HIV, COPD, smoking, alcohol consumption and underweight were significant risk factors for patient being Extra pulmonary TB positive.